PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XIDALAM PEMBELAJARAN TIK - Agung Wicaksono, - (2009)
Research " Penerapan Model Pembelajaran Inkuiri Terbimbing Terhadap Peningkatan Hasil Belajar Siswa Kelas XI Dalam Pembelajaran TIK " is intended for the improvement of student learning TIK model for the implementation of guided inquiry to know the level and effectiveness of learning models guided inquiry conducted. Study results include the results of study on the cognitive domain, psikomotor domain , and afektifdomain. Results cognitive domain learning from an average gain of one to three series. While the study results on afektif domain and psikomotor obtained from the average score of each aspect of the series one to three series. This research was conducted in Bandung UPI Laboratory High School with a population in this research is a class XI student academic year 2008/2009 and a sample class XI IPA 2. Guided inquiry model is a model of learning based on students (student-Centered-strategy) in which groups of students search for answers to the questions in a group structure and the procedures outlined clearly. Research method used is Kuasi experiments conducted in three series. Instruments used include (I) student achievement to cognitive aspects (2) student activity guidelines observations (3) Guidance teacher observation (4) guidelines and observations psikomotor aspects afektif. The research results obtained that the percentage increase for the cognitive aspects of each series is 11%, 11% and 13%, aspect psikomotor students in each series with 54%, 75% and 75% and aspect afektif students in each series with 65%, 66% , and 68% Based on the processing and analysis of data obtained information that the application of the model of learning guided inquiry affect the improvement of student learning.